Identification, assessment and recognition of non-formal learning in Spain - Castillo, Juan José [Verfasser]; Alas-Pumarino, Andres [Verfasser]; Santos, Maximiano [Verfasser] (Office for Official Publications of the European Communities, 2000)
This report is the Spanish contribution to CEDEFOP's project on identification, assessment and recognition of non-formal learning, which was initiated in 1997. Studies in this field have been conducted in a majority of Member States of the European Union (EU) as well as the European Economic Area (EEA), with only Luxembourg and Iceland not yet included. Chapter 1 describes the Spanish context by looking at qualification as the point of departure; recent changes in the industrial fabric of Spain and the birth of a new social and institutional view of qualification; the reform of vocational education and training; informal learning in Spain; and the status of work experience in the social debate. Chapter 2 describes and analyzes the schemes and initiatives set up to identify, recognize, and establish the role played by nonformal learning in the social process of constructing qualifications. Five areas in which nonformal learning is recognized and assessed are addressed: the role played by nonformal learning in public employment policies; the status given to nonformal learning by the education authorities, provisions for access to the formal education system, and the scope for recognition of nonformal qualifications; the new national system of qualifications and the creation of the national institute for qualifications; certificates of occupational proficiency; and recognition of nonformal learning within the field of collective bargaining. Chapter 3 considers the direction in which recognition of work-based learning will move, including certificates of occupational proficiency and vocational titles. Chapter 4 draws conclusions. (BIBB-Doku)
Keywords: S 2.2.4.4 Anerkennung non-formaler Qualifikationen; S 2.2.4.3 Zertifizierung; L 2.1.1 Informelles Lernen; L 2.1.3 Erfahrungslernen; I 2.2.1 Westeuropa; Anerkennung; Zertifizierung; Qualifikation; Informelles Lernen; Lernen am Arbeitsplatz; Erfahrungsorientiertes Lernen; Spanien